2014
DOI: 10.2169/internalmedicine.53.2871
|View full text |Cite
|
Sign up to set email alerts
|

Protracted Febrile Myalgia Syndrome in a Japanese Patient with Fasciitis Detected on MRI

Abstract: Protracted febrile myalgia syndrome (PFMS) is a rare manifestation of familial Mediterranean fever characterized by prolonged severe myalgia. We herein describe a case of PFMS with fasciitis on magnetic resonance imaging. The response to corticosteroid therapy was prompt, as is typical for PFMS. An MEFV gene analysis revealed the patient to be homozygous for E148Q and compound heterozygous for P369S-R408Q. This is the first case report of a Japanese patient with PFMS. MRI findings may help to diagnose such cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Aseptic meningitis [32] also has been described in Japanese patients with FMF. Myalgia particularly affects the legs, and protracted febrile myalgia is considered to be one of the muscular manifestations of FMF [33]. It can be resolved with prednisolone treatment.…”
Section: Clinical Manifestations Of Japanese Fmf Patientsmentioning
confidence: 99%
“…Aseptic meningitis [32] also has been described in Japanese patients with FMF. Myalgia particularly affects the legs, and protracted febrile myalgia is considered to be one of the muscular manifestations of FMF [33]. It can be resolved with prednisolone treatment.…”
Section: Clinical Manifestations Of Japanese Fmf Patientsmentioning
confidence: 99%
“…A recent case report from Japan described a 22-year-old man with PFMS who showed thickening of the fascia on short-time inversion recovery (STIR) images of plain MRI [ 7 ]. The authors suggested that inflammation in the setting of PFMS occurs in the fascia rather than the muscle fiber, and that the myalgia experienced by affected patients is caused by fasciitis.…”
Section: Discussionmentioning
confidence: 99%
“…In 1988, Schapira et al [ 6 ] evaluated the ultrastructural muscle tissue features of PFMS and noted a large deposition of collagen fibers during the acute stage. More recently, Fujikawa et al [ 7 ] described a finding of fasciitis on magnetic resonance imaging (MRI) in a patient with PFMS.…”
Section: Introductionmentioning
confidence: 99%
“…Monogenic interferonopathies, such as proteasome-associated autoinflammatory syndromes and stimulator of interferon genes (STING)-associated vasculopathy with onset in infancy syndrome, can mimic JDM 78 , 79 . Protracted febrile myalgia is a rare manifestation of familial Mediterranean fever characterized by prolonged severe and symmetric muscle pain, fever and elevated inflammatory markers that can also mimic JIIM 80 .…”
Section: Clinical Phenotypesmentioning
confidence: 99%